Tachyon potential in bianchi type-V universe - Singh T.; Chaubey R. (My University, 2025)
The solution for a tachyon potential has been obtained for a Bianchi type-V universe in two forms (power-law and exponential type). © 2012 Pleiades Publishing, Ltd.